Micro, Small, and Medium Enterprise Finance : Improving Access to Finance for Women-Owned Business in India - International Finance Corporation (International Finance Corporation, Washington, DC, 2017)
Lending to women-owned micro, small, and medium enterprises (MSMEs) as a distinct segment is still unexplored when compared to lending to MSMEs in India. Due to a lack of segmental focus and, perhaps, due to a higher perception of risk, formal financial institutions have made little effort to better understand this segment. There is a lack of awareness among bankers of the potential business opportunity presented by this segment. One reason for this is the lack of data that will help present a business case to target this emerging sector. In cases where formal institutions have created women-MSME targeted credit schemes, lack of awareness and limited outreach (especially in rural areas) has meant that the impact is limited. IFC’s work in this area aims to (a) build awareness about opportunities in access to finance for women-owned businesses; (b) demonstrate commercial viability of offering financial services to this sub-segment; and (c) strengthen capacity of the financial sector to offer targeted financial services to women entrepreneurs. As part of its intervention in this sector, IFC organized a roundtable with representatives from banks, non-banking financial institutions, and industry associations to understand perspectives and discuss financial access for women-owned businesses. The discussion began to build awareness of the opportunities in the women entrepreneurs’ segment for financial institutions, and best practices involved. This report aims to assess the gap in demand and supply of finance, highlight the opportunity in serving women entrepreneurs, and catalogue initiatives taken by financial institutions in access to finance for women-owned businesses in India. The report presents the findings of a scoping study based on secondary research and primary interviews, together with key themes of the roundtable discussion, and recommends potential interventions by financial institutions to address the lack of access to formal finance for women-owned businesses in India.